Induksi Pertumbuhan Eksplan Endosperm Ulin dengan IAA dan Kinetine - -, HIDAYAT (AGRITROP, 2007)
The aims of this research for examining the effect of concentrations of Indole Acetic Acid (IAA) and Kinetine onthe growth of ulin. The research using Murashige and Skoog medium was conducted in Biotechnology Laboratoryof Agriculture Faculty, Tanjungpura University from June 2003 to May 2004. All treatments were arranged inrandomized complete design with ten treatments and four replications. The variable of this research was scoring oncallusformation, time of callusformation (days) and number of callus. The result showed that (5.0 ppm IAA + 6.0ppm Kinetine) and (6.0 ppm IAA + 5.0 ppm Kinetine) were better concentration combination for callus induction.The better for time of callusformation and numbers of callus were 5.0 ppm IAA + 6.0 ppm Kinetine.